The Effect of Debt Policy and Profitability on Stock Prices: Evidence from Food and Beverage Companies Listed on the Indonesia Stock Exchange - Lastari, Adria Wuri (Fakultas Hukum dan Ekonomi Bisnis, 2025)
This study investigates the effect of debt policy and profitability on stock prices of food and beverage companies listed on the Indonesia Stock Exchange. Using a quantitative approach, the study analyzes secondary data obtained from published financial statements of selected firms. Debt policy is proxied by the Debt to Equity Ratio (DER), while profitability is measured using Return on Assets (ROA). Multiple linear regression analysis is employed after satisfying classical assumption tests. The empirical results indicate that profitability has a statistically significant effect on stock prices, whereas debt policy does not exhibit a significant effect when examined individually. However, the simultaneous test reveals that debt policy and profitability jointly have a significant effect on stock prices. The coefficient of determination shows that the explanatory power of the model is relatively modest, suggesting that stock prices are influenced by various other factors beyond firm-level financial ratios. These findings imply that investors in the food and beverage sector place greater emphasis on firms’ ability to generate profits than on capital structure decisions. Nevertheless, debt policy remains relevant when evaluated in conjunction with profitability. This study contributes to the literature by providing sector-specific evidence from an emerging market context and offers practical insights for managers and investors regarding financial performance and firm valuation.